(untitled) (Journal of Humanities and Social Sciences Research, 2023)
The Police College, the factory of heroes, protectors of the homeland, and the law, is a free and discreet Iraqi military institution. It provides the Internal Security Forces with officers with high military and administrative capabilities. It is one of the oldest institutions in our dear country. The graduates of this college are responsible for citizens’ protection and security and for applying the law at home. It receives applicants who possess high physical, movement, and discipline qualifications, and who distinguish themselves from others. Among these psychological variables is high morale (which is of significant importance in the field of work since it is a measure of workers’ effectiveness and their benefit in their institutions). It is closely related to the individual’s ability to perform the high physical training students receive during their admission to the Police College. The significance of the research lies in revealing the relationship between psychological resilience and the extent to which it impacts the morale of the trainees who perform the arduous and focused exercises that are part of Police College’s training curriculum, session 68. Concerning the research problem: Represented by the fact that attaining a high and appropriate physical level requires not only continuous physical preparation, but it must also be facilitated continuously and continuously with psychological variables that effectively affect morale, thereby increasing the ability to perform physical exercises for Police College, session 68 students. The research objectives are: 1- Preparing a psychological resilience scale for Police College students, session 68. 2- Preparing a measure to raise the morale of the Police College students, session 68. 3- Identifying the reality of psychological resilience and its relationship to raising morale for physical training for Police College students, session 68. Research Assumes: There is a significant correlation between psychological resilience and raising morale for physical training for Police College students, session 68.